Stock Market Development in Sub-Saharan Africa : Critical Issues and Challenges - Adjasi, Charles Komla (IMF Working Papers; Working Paper, 2007)
This paper examines the economic importance of stock markets in Africa. It discusses policy options for promoting the development of the stock market in Africa. The results of the paper show that the stock markets have contributed to the financing of the growth of large corporations in certain African countries. An econometric investigation of the impact of stock markets on growth in selected African countries, however, finds inconclusive evidence even though stock market value traded seem to be positively and significantly associated with growth. African stock exchanges now face the challenge of integration and need better technical and institutional development to address the problem of low liquidity. Preconditions for successful regional approaches include the harmonization of legislations such as bankruptcy and accounting laws and a liberalized trade regime. Robust electronic trading systems and central depository systems will be important. Further domestic financial liberalization such as steps to improve the legal and accounting framework, private sector credit evaluation capabilities, and public sector regulatory oversight would also be beneficial.